Some fractional-order modeling and analysis of the transmission dynamics together with prevention controls - Guirao J.L.G.; Jan R.; Baleanu D.; Mohammed P.O.; Abdullah F.A.; Chorfi N. (Springer Science and Business Media Deutschland GmbH, 2025)
The purpose of the present research is to improve our understanding of how coronavirus infection spreads by creating an epidemic model that incorporates isolation and quarantine measures. The dynamics of this viral spread are represented using the Caputo?Fabrizio operator. By analyzing the equilibria of the model and utilizing the next-generation matrix method, we determine the endemic indicator, R0. The main findings demonstrate that the equilibrium without infection is locally stable when R0 is less than one and unstable otherwise. Also, we demonstrate the existence and uniqueness of the solution of our recommended model. In addition to this, we interrogate the solution pathways of the system by varying different factors, aiming to comprehend the intricate transmission of COVID-19 and visualize the crucial factors of the system that can aid public health officials in the control of the spread of infection. ? The Author(s), under exclusive licence to EDP Sciences, Springer-Verlag GmbH Germany, part of Springer Nature 2024.